Sweat Loss and Hydration Habits of Female Olympic, Varsity and Recreational Ice Hockey Players - Bigg, Jessica Lynne; Gamble, Alexander Shand Davis; Vermeulen, Tyler Fredrick; Boville, Stephanie Michelle; Eskedjian, Greg S.; Palmer, Matthew Stephen; Spriet, Lawrence L. (International Journal of Sports Medicine, 2019)
This study measured sweat losses, voluntary fluid intake, sodium balance, and carbohydrate intake of female ice hockey players during on-ice practices at the Olympic, varsity, and recreational levels. Testing was conducted on 25 Canadian Olympic players, 21 varsity, and 21 recreational players. The average sweat rate for the Olympic players (0.99±0.08 L/h) was significantly greater than both the varsity (0.67±0.05 L/h, p=0.001) and the recreational players (0.42±0.03 L/h, p<0.001), and the varsity players also had a significantly greater sweat rate than the recreational athletes (p=0.016). Total fluid intake was significantly greater for both the Olympic (p=0.001) and varsity players (p=0.007) compared to the recreational group. Only 3 of 25 Olympic players lost>1.5% BM and 4 others lost>1% BM, with no players in both the varsity and recreational teams losing>1% BM. Half of the Olympic players consumed some carbohydrate during practice, but most of the varsity and recreational players did not. In conclusion, sweat rates in female ice hockey players during practices were proportional to competitive level. Fluid intake was similar between groups and resulted in only a few athletes at the Olympic level being at risk of excess body mass loss.
Keywords: ice hockey; female; hydration; sweat; sodium; carbohydrate